2021
DOI: 10.1038/s41598-021-99917-2
|View full text |Cite
|
Sign up to set email alerts
|

Visible blue light inhibits infection and replication of SARS-CoV-2 at doses that are well-tolerated by human respiratory tissue

Abstract: The delivery of safe, visible wavelengths of light can be an effective, pathogen-agnostic, countermeasure that would expand the current portfolio of SARS-CoV-2 intervention strategies beyond the conventional approaches of vaccine, antibody, and antiviral therapeutics. Employing custom biological light units, that incorporate optically engineered light-emitting diode (LED) arrays, we harnessed monochromatic wavelengths of light for uniform delivery across biological surfaces. We demonstrated that primary 3D hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 42 publications
7
43
1
Order By: Relevance
“…Also, in studies on a phage, Tomb et al found approximately a factor of 10 in the log-reduction dose in solutions without riboflavin (1021 J/cm 2 ) and in nutrient medium (113 J/cm 2 ) [40]. This observation of the influence of the medium or the riboflavin concentration on the virus inactivation is quantitatively and qualitatively confirmed by several other authors [37,43,45,48,49,62,63]. In contrast, there is not one report with a higher log-reduction at lower riboflavin concentrations, when different concentrations or media were employed.…”
Section: Discussionsupporting
confidence: 60%
“…Also, in studies on a phage, Tomb et al found approximately a factor of 10 in the log-reduction dose in solutions without riboflavin (1021 J/cm 2 ) and in nutrient medium (113 J/cm 2 ) [40]. This observation of the influence of the medium or the riboflavin concentration on the virus inactivation is quantitatively and qualitatively confirmed by several other authors [37,43,45,48,49,62,63]. In contrast, there is not one report with a higher log-reduction at lower riboflavin concentrations, when different concentrations or media were employed.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, Oh et al [25], showing the antiviral effect of blue light on SARS-CoV-2 already-infected cells (450 nm, 5.56 mW/cm 2 , 1.6, 5, 10 J/cm 2 ), reported that an antiviral effect was associated with reactive oxygen species (ROS) production, endoplasmic reticulum stress and autophagy progression, inhibiting apoptosis and promoting cell survival. These studies employed minor irradiance with respect to those employed in the current study (0.1 W/cm 2 ), nevertheless the fluence (3 J/cm 2 ) was comparable [25] or higher [12,24]. Our results failed to highlight an antiviral effect in already-infected cells as the three papers cited above showed, however the different virus strains treated, and the different devices employed, could account for the results.…”
Section: Discussioncontrasting
confidence: 69%
“…LED lamps at 450, 454 and 470 nm (CW) were able to cause a decrement in the viral RNA quantity when infected Vero E6 cells were irradiated (450 nm, 0.04 W/cm 2 ; 12.5 J/cm 2 ; 454 nm, 0.04 W/ cm 2 ; 10 J/cm 2 ; 470 nm, 0.04 W/ cm 2 , 20 J/cm 2 ) and relevant decreases were reported, especially at 48 h post-treatment [12]. Stakos et al [24] employed LED light with a peak at 425 nm (dose ranging from 7.5 to 60 J/cm 2 , 50 mW/cm 2 ), on three coronaviruses, i.e., SARS-CoV-2, SARS-CoV-1 and MERS-CoV [24]. When both Vero cells and 3D human tracheal/bronchial-derived epithelial tissue were infected with SARS-CoV-2 and then irradiated, a reduction in viral infection was observed.…”
Section: Discussionmentioning
confidence: 93%
“…Vero E6 and A549 cells were purchased from ATCC. Vero E6 cells were maintained as previously described (Stasko et al, 2021b). A549 cells were maintained according to ATCC instructions.…”
Section: Methodsmentioning
confidence: 99%
“…A549 cells were maintained according to ATCC instructions. Human adenovirus type 5 (VR-5) was acquired from the ATCC and passaged as previously described (Stasko et al, 2021b).…”
Section: Methodsmentioning
confidence: 99%